A educação de jovens e adultos na educação profissional: os cenários da produção acadêmica e a visão de estudantes de uma escola pública de Santa Maria - RS - Trindade, Luane Nunes (2024)
This dissertation was developed as part of the Academic Master's Degree in Professional and Technological Education in the Teacher Training line and aims to understand the teaching of History in PROEJA and the contribution of this component as a trainer of social subjects. Initially, we analyzed the panorama of global scientific production on the subject of professional education for young people and adults by means of a bibliometric analysis. To do this, we selected articles from the Web of Science database published between 2009 and 2024. Next, we sought to identify the scenario of academic productions on Teacher Training for EFA, through a documental research, of a scientometric nature, in the Database of the Brazilian Digital Library of Theses and Dissertations, using the terms “teacher training” and “Professional Education” as descriptors, in the time frame of 2013-2023. Complementing the research, we also sought to understand the use of digital technology resources for young people and adults in Vocational Education in the same database. Finally, we sought to analyze what the students of a PROEJA training course think about the importance of teaching History for their training, based on a case study, as well as mapping the potentialities and challenges they perceive throughout their training, using a survey-type questionnaire as a data collection instrument. Based on the results collected throughout the work, it can be said that the European community is one of the largest producers of knowledge in the area and that research mainly relates youth and adult education to the world of work. When analyzing the academic research scenario on Teacher Training for Vocational and Technological Education, there is a slight upward trend in the number of studies, most of which come from postgraduate programs: PPGEPT/UFSM and MPET/IFAM. When investigating the use of TDIC in the context of PROEJA, it can be said that although digital technologies have been occupying space in the classroom context, little is still discussed about their use by mature adults, which is an opportunity for study. Finally, when investigating the profile of students on a professional education course in the PROEJA modality, we realized that the students who enter this modality of education are looking not just for a diploma, but for a profession, and that they have difficulties reconciling their studies with work and family. They also point out the contributions of history teaching to their education and recognize themselves as social subjects.